(untitled) (Research, Society and Development, 2021)
The study on Sustainable Development is a scientific field that has been developed and worked on in several aspects, characterized as multidisciplinary and multifaceted. Sustainability indicators are essential tools in an attempt to measure it, driven by the desire to reach the SDGs, with cities, management and the population being potential allies for their promotion. In this sense, understanding and discussing the complexity that surrounds this theme is a condition for effectively advancing this field of research in depth. Based on this, this article aimed to analyze the recent scientific production on the Sustainable Development Goals, Sustainability Indicators and Sustainable Municipal Management, in order to understand them and identify the main contexts that orbit about the topics under study. For this, the Web of Science platform was used for data collection, adopting the systematic literature review as a research procedure and as analysis tools, the CitNetExplorer software was used. The results allowed to categorize the works explored in 7 clusters, grouped according to their central theme, thus enabling the achievement of the proposed objective. The database used also revealed themes transversal to the proposals in this study, which could significantly assist in the development of other research.